Feminist Standpoint and Question of Women Participation in Decision-Making, in Nepal - Pandey, Binda (Dhaulagiri Journal of Sociology and Anthropology, 2016)
Feminist standpoint theory emerged in the 1970s. As a feminist critical theory it focuses on the relationship between the production of knowledge and practices of power. It can be considered as a blended form of Marxist feminist, critical theory and a range of social scientific disciplines. Feminist standpoint helps to understand and explain the world through marginalized, subordinated and oppressed women's point of view in the society considering them as knowledgeable. It is the process of mainstreaming their knowledge, skill and experiences. Feminist standpoint focuses on power relations, which is broadly cultivated on cultural values and assigned gender role. In this context, feminist standpoint could be a theoretical basis to mainstream women's knowledge, skill and experiences, instead of conventional way of thinking and doing things with taking into account the knowledge and experiences of dominant groups.